Evolution, Cognition, and Horror: A Précis of Why Horror Seduces (2017). (13th August 2018) - Clasen, Mathias
Abstract : Why are people attracted to scary entertainment, to stories and leisure activities designed to evoke negative emotion? How does such entertainment work, and why does it work? Why do we respond with genuine fear to flickering light on a screen? Why do our stories brim with danger and horror and monsters, sometimes far-fetched and utterly implausible monsters? The culmination of that research, so far, is my 2017 monograph Why Horror Seduces. In this article, I will introduce that work, which is the first book-length study of horror from an evolutionary perspective. After a brief introduction to the subject matter, I explain the main theoretical assumptions of the book. I then give a few examples of evolutionary horror theory in analytical and interpretative practice and offer some considerations on the adaptive function of horror. Finally, I reflect on the challenges and benefits of interdisciplinary work and point the way toward future studies.